Effects on Berry Shrinkage in Vitis vinifera. L cv. ‘Merlot’ From Changes in Canopy/Root Ratio: A Preliminary Approach - Gutiérrez-Gamboa, G.; Pardo, C.; Moreno-Simunovic, Y. (South African Journal of Enology and Viticulture, 2018)
A trial was conducted to find a possible relationship between the canopy/root ratio and the incidence and severity of premature berry shrinkage, and to propose an alternative to avoid this phenomenon in ‘Merlot’ grapevines. The ratio was changed by cutting foliage at a certain height 15 days before véraison, and by delaying the removal of trunk shoots. Treatments were the control (T1), 50% foliage area of control (T2), 75% foliage area of control (T3), and delayed trunk shoot removal (T4). Foliage area and the canopy/root ratio were lower in the T2 and T3 treatments. T4 was ineffective in changing the parameters. The incidence of berry shrinkage was lower for the T2 and T3 treatments, with the percentage of affected plants dropping from the 52% of the control to 22.9% and 31.3% for T2 and T3 respectively, and from 52.4% of the affected bunches to 16.6% and 21.2% for the same treatments respectively. The percentage of affected bunches falling into the range of moderate to severe damage fell from the 24% of the control to 5.2% and 3.9% for T2 and T3 respectively. Therefore, it is possible to avoid the incidence and severity of berry shrinkage by decreasing the canopy/root ratio in ‘Merlot’ grapevines.